Elementary School Students’ Perceptions of Physical Education Learning and Its Relation to the Development of Basic Motor Skills - Tuhfatul Amin; Ainur Rasyid; Mas'odi Mas'odi (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Physical Education, Sports, and Health are vital in developing elementary school students' fundamental motor skills. However, previous studies have often examined students' perceptions of physical education and motor skill development separately, overlooking how students' subjective experiences and attitudes toward Physical Education, Sports, and Health directly relate to measurable motor skill outcomes. Methodology: The research employed a quantitative survey involving 40 randomly selected 5th-grade elementary school students. Data were collected using a closed-ended Likert-scale questionnaire designed and validated for elementary students, measuring perceptions across six dimensions, and an observation checklist aligned with the national curriculum indicators to assess basic motor skills. Main Findings: The results showed that 75% of students reported high enjoyment of Physical Education lessons, and 65% actively participated in physical activities during class. Observations indicated that most students demonstrated strong locomotor and manipulative skills, though balance and coordination still required development. The analysis suggested that students who reported higher enjoyment and perceived benefits of Physical Education tended to show better motor skills, indicating a positive correlation between perception and skill development. Novelty/Originality of this study: The findings highlight the need for more inclusive and engaging Physical Education, Sports, and Health curricula that foster enjoyment and systematically develop under-emphasized skills like balance and coordination. This study contributes novel empirical evidence linking students' subjective perceptions with objective motor skill outcomes in Indonesian elementary education, an area largely overlooked in prior research.